In situ measurements of micronutrient dynamics in open seawater show that complex dissociation rates may limit diatom growth. Issue 1 (December 2018) - Baeyens, Willy; Gao, Yue; Davison, William; Galceran, Josep; Leermakers, Martine; Puy, Jaume; Superville, Pierre-Jean; Beguery, Laurent
Abstract In this firstin situ study of the dynamic availability of phytoplankton micronutrients, a SeaExplorer glider was combined with Diffusive Gradients in Thin Films and deployed in the Mediterranean Sea. On the basis of their labile metal complex pools, we discovered that Fe and Co can be potentially limiting and Cu co-limiting to diatom growth, contrary to the generally accepted view that phosphorus (phosphate) is the growth limiting element in the Mediterranean Sea. For flagellates and picoplankton, phosphorus remains the main element limiting growth. Ourin situ measurements showed that organic complexes of Fe and Cu (>98% of total dissolved concentration), dissociate slower than inorganic complexes of Co, Cd and Ni (>99% of total dissolved concentration being free ions and inorganic complexes). This strengthens the potential growth limiting effect of Fe and Cu versus phosphate, which is present as a free ion and, thus, directly available for plankton.